PENINGKATAN KEMAMPUAN MENGERJAKAN OPERASI HITUNG PENJUMLAHAN DAN PENGURANGAN MENGGUNAKAN METODE DEMONSTRASI DAN KODOK MELOMPAT PADA SISWA KELAS 1 SD NEGERI 060912 TAHUN 2024/2025 - Nevi Melani Siregar; Marah Doly Nasution; Dermawan Nasution (STKIP Subang, 2024)
The purpose of this study was to improve the ability to do addition arithmetic operations using the demonstration method and the Jumping Frog media for students in grade 1 semester 1 of SDN 060912 Medan in the 2024/2025 academic year. The study was conducted using the stages in Classroom Action Research (CAR), namely planning, implementation, observation, and reflection. The study was conducted in two cycles. Based on the description of the implementation of the action, research results, and discussion, data was obtained on an increase in the ability to do calculations in each cycle. In cycle I, students' ability to do addition arithmetic operations in the pre-cycle was 40.88%, increasing by 21% to 61.88% and increasing in cycle II by 23.8%, reaching 85.68%. The conclusion is that through the demonstration method and the jumping frog media, the ability to do addition calculations in mathematics learning in grade I of SDN 060912 Medan in semester 1 of the 2024/2024 academic year can be improved.